My Baby Takes the Morning Train: Gender Identity, Fairness, and Relative Labor Supply Within Households - Anthony Lepinteur; Sarah Flèche; Nattavudh Powdthavee (Institute for the Study of Labor (IZA), 2016)
The current study argues that women's decision to leave the labor force at the point where their income exceeds their husbands' income may have less to do with gender identity norm (Bertrand et al., 2015) and more to do with what women think is a fair distribution of relative working hours within the household. Using three nationally-representative data, we show that life satisfaction is significantly lower among women whose work hours exceed their partners, holding the share of wife's income constant. Men, by contrast, are not affected by working longer or fewer hours than their wives.
Keywords: I31; J12; J22; 330; fairness; gender identity; life satisfaction; relative income; working hours; labor supply